Analysis of Islamic Religious Education Teacher’s Strategy in Forming Students' Learning Culture at State Senior High School 4 Palu - Sagaf S. Pettalongi; Badrin Badrin; Ahmad Syahid; Saepudin Mashuri (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2022)
A learning culture makes a considerable contribution in welcoming the new millennium era because the abilities developed through a learning culture are physical and spiritual abilities. The development of these physical and spiritual abilities includes: in terms of knowledge, skills, prowess, life values, attitude, dedication, and discipline. Therefore, our learning culture is an effort to answer challenges to problems that arise. Therefore, the learning culture must be carried out optimally. This research used qualitative research, with data data collection techniques includes observation, interviews, and documentation, while the data analysis techniques used are data reduction, data presentation, and concluding. The study results show that in forming a learning culture at a State Senior High School, such curricular activities include: Instilling religious and disciplinary character in preliminary activities, instilling religious and disciplinary character in core activities, and Instilling a religious and disciplined learning culture in closing activities. Cultivating a culture of religious learning and discipline through habituation in daily activities, namely: getting used to time discipline, habituation of congregational noon prayers at school, increasing a sense of care and courtesy, as well as in extracurricular activities. Learning culture is a good habit that is tried to be done as habituation, and then it will become a habit that continues to be carried out daily. In this case, the teacher applies it in two ways, namely when learning takes place and extracurricular so that the culture of religious learning and discipline sticks and is integrated into student behavior.